The wage under attack. Employment policies in Europe (Frankfurt am Main, 2013)
"Challenging the widespread view of the continental model of social protection as a «corporatist-conservative» system, this book stresses the creative thrust of the two major institutions of the Bismarckian tradition: the social contribution that finances the socialised wage, and the qualification system that liberates workers from the labour market. These institutions have come under attack over the past two decades via European Employment Strategy policies aimed at imposing the Beveridgean model. And the European Union is using the current economic crisis to justify stepping up this reform process. The conceptual framework proposed in this volume provides the basis for a critical examination of the interrelated developments in European integration and national policies on employment and social protection. As well as contributing to a sociology of monetary resources, it highlights the emancipatory potential of the continental tradition of the socialised wage, and demonstrates the negative implications of the European Union-led reforms."